Portable non-invasive glucose and haemoglobin level monitoring incorporated along with multi paramonitoring system - Kevin Amos, A; Rajalakshmi, T; Raja, D (IOP conference series. Materials Science and Engineering, 2020)
Contemporary wireless technology gives a lot of new prospects for monitoring vital parameters. This paper presents a compact vital signs monitoring system using non-invasive optical sensors alone which is currently not present at disposal. An android app called multi para-tracker (MTP) is developed which connects to the device via Bluetooth which displays the value of the scrutinized parameters. A microcontroller ATmega328p connects all the sensors and Bluetooth and controls the system to work as programmed in the Arduino IDE software. This feature has a colossal advantage as it does not restrict the mobility of the patient and also diminutions the waiting time of the patients in hospitals. The system monitors vital signs measurement include Heart rate, oxygen saturation level in blood, Respiration rate, Blood Pressure, Temperature, Haemoglobin count and Blood Glucose level. This system can most probably exterminates the erstwhile procedure of extracting blood from the patients for testing the blood glucose level and also for haemoglobin count measurement in the imminent. Hence the developed prototype is tested with 30 different subjects and calibrated accordingly to show almost accurate results when compared to the existing techniques.